Synthèse et caractérisation de nouveaux géopolymères à base de géomatériaux naturels et de rejets industriels - Ayoub AZIZ (Faculté des Sciences de Rabat, 2021)
The cement industry today faces a major environmental problem due to CO2 emissions and high energy consumption. The objective of this research is to synthesize alternative geopolymers to Portland cement based on geomaterials and industrial waste. In the course of this work, three actions were carried out. (i) The synthesis of geopolymers based on Moroccan pozzolan and hydrated lime, revealing that the addition of 8% slaked lime to the pozzolan favors the formation of Al-C-S-H gel, leading to the obtaining of a geopolymer with encouraging physico-chemical properties (Rc = 23,05 MPa ; Vp = 2,21 km/s ; D = 2,05 g/cm³ ; P = 5,13% ; A = 2,49%). (ii) The synthesis of geopolymers based on French pozzolan and blast-furnace slag, showing that the addition of 50% of L1 slag, of a more magnesian composition to that of L2 slag, allowed to obtain a geopolymer of high physicomechanical performance (Rc =105,7 MPa ; Vp =5,1 Km/s ; D =2,28 g/cm3 ; P =8,80%). (iii) The synthesis of geopolymers based on perlite and kaolinic clay from Morocco, stating that the addition of 10% of the calcined kaolinic clay to the perlite significantly improved the characteristics of the geopolymers, giving a performing geopolymer at 28 days: Rc = 36,36 MPa, Vp = 3,3 Km/s, Mv = 1730 Kg/m3, P = 17,66%. These results are promising for the synthesis of geopolymers with technological characteristics required by Moroccan construction standards.
Synthesis and characterization of new geopolymers based on natural geomaterials and industrial wastes
Keywords: Sciences de la Terre; Sciences de la Terre